The landscape of genetic variations in non-syndromic primary ovarian insufficiency in the MENA region: a systematic review - Allouch, Asma; Al-Barazenji, Tara; Al-Shafai, Mashael; Abdallah, Atiyeh M. (Frontiers in Endocrinology, 2024)
Introduction Premature ovarian insufficiency (POI) is a primary cause of infertility with variable clinical manifestations. POI is a multifactorial disease with both environmental and known genetic etiologies, but data on the genetic variations associated with POI in the Middle East and North Africa (MENA) region are scarce. The aim of this study was to systematically review all known genetic causes of POI in the MENA region. Methods The PubMed, Science Direct, ProQuest, and Embase databases were searched from inception to December 2022 for all reports of genetic variants associated with POI in the MENA region. Clinical and genetic data were collected from eligible articles, and ClinVar and PubMed (dbSNP) were searched for variants. Results Of 1,803 studies, 25 met the inclusion criteria. Fifteen studies were case-control studies and ten were case reports representing 1,080 non-syndromic POI patients in total. Seventy-nine variants in 25 genes associated with POI were reported in ten MENA countries. Of the 79 variants, 46 were rare and 33 were common variants. Of the 46 rare variants, 19 were pathogenic or likely pathogenic according to ACMG classification guidelines and ClinVar. No clear phenotype-genotype association was observed. Male family members carrying pathogenic variants also had infertility problems. Discussion To our best knowledge, this is the first systematic review of the genetic variants associated with POI in the MENA region. Further functional studies are needed to assess the disease-causing molecular mechanisms of these variants. Knowledge of the genetic basis of POI in the Middle East could facilitate early detection of the condition and thus early implementation of therapeutic interventions, paving the way for precision medicine options in specific populations.